2010
DOI: 10.1007/s11262-010-0457-8
|View full text |Cite
|
Sign up to set email alerts
|

Complete nucleotide sequence and taxonomy of Sugarcane streak mosaic virus, member of a novel genus in the family Potyviridae

Abstract: The complete genomic sequence of a Pakistani isolate of Sugarcane streak mosaic virus (SCSMV-PAK) is determined to be 9782 nucleotides in length, excluding the 3' poly(A) tail, and it comprises a large open reading frame encoding a polyprotein of 3130 amino acid residues. The deduced polyprotein is likely to be cleaved at nine putative protease sites by three viral proteases to ten mature proteins. Conserved motifs of orthologous proteins of other potyviruses are identified in corresponding positions of SCSMV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
38
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 25 publications
2
38
0
1
Order By: Relevance
“…The result revealed that the conserved motif, GGAAAAAAA was found at the nucleotide position 3085-3093 which is similar to that of SCSMV-PAK reported by Xu et al (2010). The deduced 139 aa of PIPO of THA-NP3 was obtained from 420 bp in the +1 frame at the nucleotide position 3091-3510 as reported by Chandran and Gajjeraman (2015).…”
Section: Incidence Of Scsmv In Surveyed Sugarcane Fieldssupporting
confidence: 77%
See 3 more Smart Citations
“…The result revealed that the conserved motif, GGAAAAAAA was found at the nucleotide position 3085-3093 which is similar to that of SCSMV-PAK reported by Xu et al (2010). The deduced 139 aa of PIPO of THA-NP3 was obtained from 420 bp in the +1 frame at the nucleotide position 3091-3510 as reported by Chandran and Gajjeraman (2015).…”
Section: Incidence Of Scsmv In Surveyed Sugarcane Fieldssupporting
confidence: 77%
“…All selected isolates yielded the expected 1094 bp RT-PCR product, from which an isolate from Kamphaeng Saen District, Nakhon Pathom Province, designated as THA-NP3 ( Figure 1a) was subjected to full length genome sequencing. Nine putative cleavage sites of the polyprotein were identified in comparison to the putative sites of SCSMV-PAK polyprotein (Xu et al, 2010) and some others (Figure 3). All cleavage sites of THA-NP3 proteins as well as the positions of the amino acids were similar to those of the SCSMV isolates, PAK, ID, JP1, JP2 and TPT but not IND671.…”
Section: Incidence Of Scsmv In Surveyed Sugarcane Fieldsmentioning
confidence: 99%
See 2 more Smart Citations
“…SCSMV has flexuous filamentous particles (890 9 15 nm) containing a single-stranded positive-sense RNA genome of approximately 10 kb. The SCSMV genome has a single open reading frame that is translated in to a large polypeptide and subsequently cleaved into functional proteins [7,8].…”
mentioning
confidence: 99%